The State Response toward the Existence of HTI: An Analysis from Social Movement Study Approach - Hasbi Aswar; Danial Bin Mohd Yusof; Rohana Binti Abdul Hamid (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2020)
Abstract As a global Islamic political group, Hizb ut-Tahrir (HT) has experienced many kinds of state coercive responses due its ideas that considered radical and threatening the existing modern political systems. In many places, this group has been rejected and criminalized by regimes either in Muslim majority states or in the Western states. The same experience has also been faced by HT in Indonesia that went through the change of state policy from accommodating to repressive approach. This study will focus to elaborate the response of the Indonesian government toward HTI from the lens of social movement studies by using state repression concept. This article uses the explanatory method analysis and collects data mainly from literature. This article argues that the state has used several methods to repress HT such as issuing an extraordinary law in dissolving HTI; intimidating HTI`s supporters and activists and stigmatizing or discrediting HTI image. As the result, in 2017 Indonesian government dissolved HTI, then HTI became one of forbidden organizations in Indonesia.